Cobalt Nanoparticles Encapsulated in Nitrogen-Doped Carbon Nanotube as Bifunctional-Catalyst for Rechargeable Zn-Air Batteries - Liu, Yang; Dong, Peng; Li, Mian; Wu, Hao; Zhang, Chengxu; Han, Lina; Zhang, Yingjie (Frontiers in Materials, 2019)
Developing highly efficient and low-cost non-precious-metal electrocatalysts toward oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) is crucial for improving the performance and economic outlook of alkaline-based rechargeable Zinc-air battery technologies. In this work, a nitrogen-doped carbon nanotube encapsulated with metallic cobalt nanoparticles (Co@NC) was synthesized through a facile method and subsequent pyrolysis treatment. The field emission scanning electron microscope, high resolution transmission electron microscopy, Raman spectra investigations demonstrate that the presence of Co induces the formation of carbon nanotube during the pyrolysis process and increase degree of graphitization of carbon nanotubes. The reversible oxygen electrode activity can be evaluated by the difference of OER and ORR metrica ΔE. The Co@NC exhibit a ΔE value of 0.91 V, less than those of Pt/C (1.1 V) and nitrogen-doped carbon (1.17 V). The primary Zn-air battery based on Co@NC display an open-circuit potential 1.4 V, a high power density of 137 mW cm-2, and superior high energy density of (708.3 mAh·kgZn-1 and 868.9 Wh·kgZn-1 at 10 mA·cm-2), superior to that of the commercialized Pt/C.